Nitro-Fatty Acids: New Drug Candidates for Chronic Inflammatory and Fibrotic Diseases - Schopfer, Francisco J. (Nitric Oxide, 2018)
Nitrated oleic acid (NO(2)-OA) was first identified in 2003, and after the characterization of its formation and thiol reactivity, it was used as a prototypical molecule to investigate the physiological actions of endogenous nitrated fatty acids (NO(2)-FA). Based on in vitro observations showing significant activation of cytoprotective and anti-inflammatory signaling responses by NO(2)-FA, experiments were designed to determine their pharmacological potential. Supported by strong intellectual protection and favorable pharmacokinetic and pharmacodynamic data, 10-NO(2)-OA (CXA-10) underwent pharmaceutical development as a drug to treat fibrotic and inflammatory diseases. NO(2)-FA are at the intersection of three unconventional drug candidate classes that include 1) fatty acids, 2) metabolic intermediates and 3) electrophilic molecules. These three groups use different scaffolds for drug development, are characterized by broad activities and are individually gaining traction as alternatives to mono-target drug therapies. In particular, NO(2)-FA share key characteristics with currently approved pharmacological agents regarding reactivity, distribution, and mechanism of action. This review first presents the characteristics, liabilities, and opportunities that these different drug candidate classes display, and then discusses these issues in the context of current progress in the preclinical and clinical development of NO(2)-FA as drugs. Lessons learned from the novel approaches presented herein were considered early on during development to structurally define and improve NO(2)-FA and their disease targets.